Pengaruh Digital Banking dan Kualitas Layanan Terhadap Kepuasaan Nasabah pada Bank Swasta di Jakarta - Anggun Rianda Putri; Abdul Hoer (Politeknik Kebangsaan, 2026)
Technological developments have encouraged the banking sector to adopt digital services to improve customer satisfaction. Digital banking enables faster, more convenient, and more efficient transactions, while service quality remains a crucial factor in building a positive customer experience. This study aims to analyze the influence of digital banking and service quality on customer satisfaction at private banks in Jakarta.The research method used was a quantitative approach using a survey technique. Data were collected through questionnaires distributed to 150 private bank customers in Jakarta who had used digital banking services. The sampling technique used was purposive sampling. Data analysis was conducted using validity tests, reliability tests, classical assumption tests, multiple linear regression, and t-tests and F-tests. The results show that digital banking has a positive and significant effect on customer satisfaction. Service quality also has a positive and significant effect on customer satisfaction. Simultaneously, digital banking and service quality significantly influence customer satisfaction at private banks in Jakarta. This demonstrates that improving the quality of digital systems and responsive service can increase customer satisfaction. Keywords: digital banking; service quality; customer satisfaction; private banks; Jakarta